The Impact of Blockchain Technology Adoption on Audit Planning: An Exploratory Study on Saudi Audit Firms (2022-2023) - Alzahrani, Abdulaziz Ali; Alwardat, Yousef Ali; Wazzan, Mohammad Aboalkar (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to (1) examine the extent of external auditors' knowledge of blockchain technology and its benefits in Saudi Arabia, (2) identify the determinants and obstacles to adopting blockchain technology in Saudi Arabia, and (3) investigate the impact of blockchain technology on audit planning from the perspective of external auditors. To achieve these objectives, the researchers designed a questionnaire consisting of 48 questions divided into four sections: demographic information, the benefits of blockchain technology for the accounting and auditing profession, the determinants and obstacles to blockchain adoption, and the impact of blockchain technology on audit planning. The questionnaire was distributed to a sample of 209 external auditors working in audit firms across Saudi Arabia. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) with appropriate statistical methods. The findings reveal that external auditors possess a high level of knowledge about the benefits of blockchain technology but identify several regulatory, environmental, and technological challenges hindering its adoption in audit firms and among their clients. Moreover, external auditors expect blockchain technology to significantly influence the identification and selection of audit procedures during the planning phase. The study recommends that regulatory and professional bodies in Saudi Arabia issue standards and guidelines to manage blockchain technology adoption. It also emphasizes the need for further research on blockchain’s impact on the auditing and accounting professions due to its emerging nature.
Keywords: Blockchain; Smart Contracts; Audit Planning; External Auditor; Audit Procedures